2013
DOI: 10.3839/jabc.2013.018
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Differentiation of Saccharomyces cerevisiae by Ketoconazole Treatment

Abstract: Azole fungicides are one of the most wide-spread antifungal compounds in agriculture and pharmaceutical applications. Their major mode of action is the inhibition of ergosterol biosynthesis, giving depletion of ergosterol, precursors and abnormal steroids. However, metabolic consequences of such inhibition, other than steroidal metabolitesare not well established. Comprehensive metabolic profiles of Saccharomyces cerevisiae has been presented in this study. Wild type yeast was treated either with glucose as co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…). A metabolomics study showed the depletion of lysine and other polar metabolites as an important factor in the stress response of S. cerevisiae exposed to ketoconazole (Keum & Kim ). However, the functional link between lysine depletion and azole stress responses is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…). A metabolomics study showed the depletion of lysine and other polar metabolites as an important factor in the stress response of S. cerevisiae exposed to ketoconazole (Keum & Kim ). However, the functional link between lysine depletion and azole stress responses is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…A genome-wide expression profile of Schizosaccharomyces pombe and Cryptococcus neoformans found SDH to be upregulated in response to exposure to clotrimazole and fluconazole, respectively (Florio et al 2011;Fang et al 2012). A metabolomics study showed the depletion of lysine and other polar metabolites as an important factor in the stress response of S. cerevisiae exposed to ketoconazole (Keum & Kim 2013). However, the functional link between lysine depletion and azole stress responses is unclear.…”
Section: Discussionmentioning
confidence: 99%